Tackling the various classes of nano-therapeutics employed in topical therapy of psoriasis - Salma A. Fereig; Ghada M. El-Zaafarany; Mona G. Arafa; Mona M. A. Abdel-Mottaleb (Taylor & Francis Group, 2020)
Psoriasis is a dermatological chronic skin condition with underlying autoimmune etiology. It deeply affects patients' quality of life. Therefore, it was an interesting target for researchers throughout the past years. Conventionally, the treatment options include anti-inflammatory agents, immune suppressants, biologic treatment, and phototherapy. Nanotechnology offers promising characteristics that allow for tailoring a drug carrier to achieve dermal targeting, improved efficacy and minimize undesirable effects. Being the safest route, the first line of treatment and a targeted approach, we solely discussed the use of the topical route, combined with advanced drug delivery systems for the management of psoriasis in this article. Advanced systems include polymeric, metallic, lipidic and hybrid nanocarriers incorporating different active agents. All formerly mentioned types of drug delivery systems were investigated through the past decades for the purpose of topical application on psoriatic plaques. Scientists' efforts are promising to reach an optimized formula with a convenient dosage form to improve efficacy, safety, and compliance for the treatment of psoriasis. Accordingly, it will offer a better quality of life for patients.